CHRONIC CEREBRAL ISCHEMIA. MODERN VIEW OF THE PROBLEM - T.V. Cherniy; V.I. Cherniy; D.V. Svitlytska (Клінічна та профілактична медицина, 2023)
Introduction. Chronic cerebral ischemia (CCI) is considered a syndrome that develops as a result of a slowly progressive reduction in cerebral blood flow. This reduction occurs due to the gradual accumulation of ischemic and secondary degenerative changes in the brain, which are caused by repeated ischemic episodes resulting from the development of atherosclerosis and arterial hypertension. These changes lead to impairment of brain functions, manifested by progressive neurological, neuropsychological, and mental disorders.